Testamentary Freedom and its Bounds in an International Succession Case - Bronušienė, Simona (Teisė, 2019)
This article presents the legal steps that should be made in an intercountry succession case dealing with testamentary succession – first of all, which court is competent to value the will; second, according to which law it should be done. The determination of applicable law is the crucial question inevaluating the will of de cujus – how much the individual was free to dispose their possession. The best way to reveal testamentary freedom in different countries is to overlook its restrictions, such as forced heirship. In the article, there are presented four systems of succession law differently restricting testamentary freedom.